PENGEMBANGAN PERANGKAT EKSPERIMEN MODULUS PUNTIR UNTUK PEMBELAJARAN FISIKA SMA - Hadi, Afdal; Sudrajad, Hendar; ', Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research was to develop are equipment of modulus twist experiment as physics teaching and learning media, resulting in a reliable and valid device used as a media of instruction. The subject of this research was an experiment equipment consist of experiment tool and guided. Data was collected by using assessment sheets of validation that has been given to validators, in which 3 validators were lecturers as expert  and 2 validators were physics teachers. The data was analyzed descriptively to find index of validity of experiment equipment. Based on the data analysis we have been concluded that an experiment equipment of modulus twist as the media in learning physics at SMA can be said valid with the very high category and feasible to be done trial at school.